1995
DOI: 10.1002/cne.903550411
|View full text |Cite
|
Sign up to set email alerts
|

Transneuronal labeling of neurons in the adult rat brainstem and spinal cord after injection of pseudorabies virus into the urethra

Abstract: Transneuronal tracing techniques were used to identify sites in the central nervous system involved in the neural control of urethral function. The distribution of virus-infected neurons was examined in the spinal cord and brainstem at various intervals (56-96 hours) following pseudorabies virus (PRV) injection into the urethra. In the lumbosacral (L6-S1) spinal cord at 56 hours, neurons containing PRV immunoreactivity (PRV-IR) were located in the region of the sacral parasympathetic nucleus (SPN), around the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(118 citation statements)
references
References 62 publications
5
110
1
2
Order By: Relevance
“…Several sites in the brainstem project serotonergic axons into the lumbosacral spinal cord. These pathways, particularly those projecting to the DL, have been implicated in the central control of bladder and urethra and recovery of bladder-external urethral sphincter coordination in SCI rats (Ding et al, 1995;Vizzard et al, 1995;Nadelhaft and Vera, 1996;Marson, 1997;Pikov and Wrathall, 2001). 5-HT-positive fibers in the DL were more densely distributed in NRP/GRP compared with OP-controls but less than in unoperated controls rats.…”
Section: Descending Modulatory Pathwaysmentioning
confidence: 90%
See 1 more Smart Citation
“…Several sites in the brainstem project serotonergic axons into the lumbosacral spinal cord. These pathways, particularly those projecting to the DL, have been implicated in the central control of bladder and urethra and recovery of bladder-external urethral sphincter coordination in SCI rats (Ding et al, 1995;Vizzard et al, 1995;Nadelhaft and Vera, 1996;Marson, 1997;Pikov and Wrathall, 2001). 5-HT-positive fibers in the DL were more densely distributed in NRP/GRP compared with OP-controls but less than in unoperated controls rats.…”
Section: Descending Modulatory Pathwaysmentioning
confidence: 90%
“…We also analyzed lumbosacral regions to determine whether these grafts would modify axonal growth from host pathways. Brainstem nuclei project corticotrophin releasing factor (CRF) containing axons (Valentino et al, 1996(Valentino et al, , 2000, serotonergic (Marson, 1997) and noradrenergic (Vizzard et al, 1995;Marson, 1997) axons to regions in the lumbosacral spinal cord, particularly the spinal parasympathetic nucleus (SPN) and the dorsolateral nucleus (DL) (Nadelhaft and Booth, 1984;Vizzard et al, 1995;Ding et al, 1997;Marson, 1997) that together coordinate the activity of the bladder and urethral sphincter (Pikov and Wrathall, 2001). Some of these modulatory pathways also project to locomotor centers in lumbar spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…(Norgren Jr and Lehman, 1989;Strack and Loewy, 1990). However, careful analyses from several transneuronal tracing studies which contain proper controls have demonstrated the use of herpes viruses to identify transneuronal connections (for example, Strack et al, 1989;Spencer et al, 1990;Jansen et al, 1992;Loewy et al, 1991;Rotto-Percelay et al, 1992;Schramm et al, 1993;Hedner et al, 1993;Vizzard et al, 1995).…”
Section: A Tool For Transneuronal Tracing Studiesmentioning
confidence: 99%
“…in several regions of the hypothalamus after injection of PRV into the LUT in animals (463,604,664). Histochemical studies using tracers also revealed that neurons in the PMC receive input from the caudal hypothalamus and that the paraventricular hypothalamic nucleus projects nonspecifically to all autonomic preganglionic motor neurons in the spinal cord, including the sacral parasympathetic and sphincter motor nuclei (270).…”
Section: Hypothalamus-transneuronal Virus Tracing Methods Have Identimentioning
confidence: 99%
“…Transneuronal PRV tracing methods have also identified many populations of neurons in the rat brain that are involved in the control of bladder (460,462,463,604), urethra (664), and the EUS (402,461,462), including the PMC (Barrington's nucleus), PAG, medullary raphe nuclei, which contain serotonergic neurons; the locus coeruleus (LC), which contains noradrenergic neurons, and the A5 noradrenergic cell group (Fig. 11).…”
Section: Axonal Projections From the Brain To The Spinal Cordmentioning
confidence: 99%